Changes in Cash: Persistence and Pricing Implications - CHEN, JEFF ZEYUN; SHANE, PHILIP B. (Journal of Accounting Research, 2014)
ABSTRACT This paper decomposes the cash component of earnings and analyzes persistence characteristics and pricing implications of various subcomponents, with particular attention to changes in cash. Changes in underlying fundamentals might dictate changes in cash to new optimal levels. Alternatively, suboptimal changes in cash might result from agency costs allowing managers’ actions to diverge from the best interests of shareholders. We predict and find that both suboptimal increases and decreases in cash bode poorly for future earnings. In fact, we find that suboptimal increases (decreases) in cash have less (greater) persistence than any of the earnings components we study, including accruals and net distributions to both shareholders and debt holders. Market efficiency tests indicate that the market severely punishes firms with suboptimal decreases in cash, but we find no evidence to support the hubris hypothesis that the market overreacts to the earnings implications of unwarranted increases in cash.